Mitochondrial ultrastructural pathology in diabetic cardiomyopathy: integrated analysis via scanning electron microscopy and 3D visualization imaging - Bo Wang; Linghao Dai; Haowei Liang; Jiayu He; Jiayi Zhou; Yang Guan; Hui Wang (Cardiovascular Diabetology)
Abstract Background Mitochondrial dysfunction plays a pivotal role in the onset and progression of diabetic cardiomyopathy (DCM). It is hypothesized that ultrastructural mitochondrial abnormalities, molecular dynamics imbalance, and bioenergetic impairments collectively contribute significantly to cardiac dysfunction. Consequently, investigating mitochondrial ultrastructural changes and metabolic disturbances is crucial for elucidating the mechanistic underpinnings of DCM. Objective This study aims to comprehensively characterize alterations in mitochondrial ultrastructure and energy metabolism in DCM and examine the interplay between these two factors. Methods High glucose-treated H9c2 cardiomyocytes and DCM model mice were analyzed via scanning electron microscopy (SEM) and 3D imaging. Three-dimensional morphometric parameters—such as Length3D, Thickness3D, Width3D, Area3D, Volume3D, Anisotropy, Flatness, and Elongation—were quantified to evaluate mitochondrial architecture. At the two-dimensional (2D) level, mitochondria-associated membrane (MAM) parameters were analyzed. Further, detailed statistical analysis was conducted on mitochondrial cristae, including cristae scores, count, width, gap size, and junction widths in myocardial tissues. Mitochondrial dynamics and autophagy-related protein expression (Mfn1, Mfn2, Opa1, p-Drp1(ser616), PINK1, Parkin1) in myocardial tissues were assessed by Western blot. Mitochondrial bioenergetics were measured by ATP content, membrane potential, mtDNA copy number, SOD levels, mitochondrial Ca2+ levels, and oxidative phosphorylation (OXPHOS) activity across Complexes I–V in myocardial tissue. Additionally, the oxygen consumption rate (OCR) of viable H9c2 cells was measured using the O2k system. Results 3D reconstruction revealed key myocardial ultrastructures—including T-tubules, sarcoplasmic reticulum (SR), intercalated discs, and mitochondria—and demonstrated significant differences in mitochondrial morphology and 3D morphometric parameters across subpopulations. Under high glucose (HG) conditions, in vitro analysis showed a reduction in mitochondrial Length3D and Anisotropy in H9c2 cells, accompanied by increases in Thickness3D, Width3D, Flatness, and Elongation. HG exposure also led to an increase in the length of MAM contact sites and the MAM-to-mitochondria perimeter ratio. In vivo, the DCM group exhibited decreased 2D morphometric parameters (length, width, area, perimeter, and shape AP), as well as reductions in 3D measurements (Thickness3D, Width3D, and Volume3D) compared to controls. No significant differences were observed in Length3D, Area3D, Anisotropy, Flatness, and Elongation between groups. 3D surface analysis revealed rough mitochondrial surfaces in the DCM group, while controls displayed smooth surfaces. Control mitochondria exhibited well-aligned, well-defined cristae, whereas DCM mitochondria showed cristae dissolution, disorganized arrangements, and vacuolization within the cristae. The DCM group also had increased cristae junction width and spacing. Additionally, megamitochondria were observed in DCM samples. The DCM group showed a significant increase in MAM contact site length and MAM-to-mitochondria perimeter ratio in myocardial tissue. Molecular analysis revealed decreased expression of fusion proteins (Mfn1, Opa1) and increased levels of p-Drp1(ser616), alongside elevated autophagy markers (PINK1, Parkin1). Bioenergetic dysfunction was evident through decreased ATP production, mitochondrial membrane potential collapse (ΔΨm), reduced mtDNA copy number, decreased SOD levels, impaired activities of complexes I/III/IV/V, and diminished basal/maximal respiration, ATP-linked respiration, and spare respiratory capacity. Conversely, mitochondrial Ca2+ levels were elevated in the DCM group, along with increased proton leakage in H9c2 cells. Conclusions This study establishes a comprehensive framework linking “3D morphology–molecular regulation–metabolic dysfunction,” highlighting the synergistic interplay between mitochondrial ultrastructural remodeling and bioenergetic failure as key drivers of DCM progression. These findings provide valuable insights into DCM pathogenesis and suggest potential therapeutic targets.